2023
DOI: 10.1021/acsomega.3c01543
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Catalytic Characteristics of Precious Metal Catalysts with Different Pt/Pd Ratios for Soot Combustion

Abstract: Soot particles in engine exhaust seriously pollute the atmosphere and endanger human health. For soot oxidation, Pt and Pd precious metal catalysts are widely used and are effective. In this paper, the catalytic characteristics of catalysts with different Pt/Pd mass ratios for soot combustion were studied through X-ray diffraction, X-ray photoelectron spectroscopy (XPS), Brunauer–Emmett–Teller analysis, scanning electron microscopy, transmission electron microscopy, the temperature-programmed oxidation reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…PGM (platinum group metal) catalysts are extremely dynamic [78,79] (Figure 5). PGMs, including platinum, palladium, and rhodium, are commonly used as catalysts for the oxidation of soot in various applications, particularly automotive exhaust systems.…”
Section: Diversity In Catalysts For Removal Of Sootmentioning
confidence: 99%
“…PGM (platinum group metal) catalysts are extremely dynamic [78,79] (Figure 5). PGMs, including platinum, palladium, and rhodium, are commonly used as catalysts for the oxidation of soot in various applications, particularly automotive exhaust systems.…”
Section: Diversity In Catalysts For Removal Of Sootmentioning
confidence: 99%
“…Soot particles, as a major component of particulate matter (PM), represent a significant air pollutant that poses serious threats to human health and the ecological environment [1,2]. In response, various countries have implemented stringent gas emission standards to control soot pollution [3]. Among the challenges in this area, reducing emissions from diesel engines, which represent the largest mobile source of soot, is significant for the environment [4].…”
Section: Introductionmentioning
confidence: 99%
“…4 Hence, transition metal oxide catalysts and manganese-based composite oxides have been considered. 5 In addition to CeMnO x and CoMnO x catalysts, 6,7 France et al . 8 demonstrated that the FeMnO x catalyst can enhance the NO conversion rate for iron ions and manganese ions by providing adsorption sites for NO, with a conversion rate as high as 80%.…”
mentioning
confidence: 99%